Factors Affecting Student Discipline: A Case Study in Junior High Schools, Indonesia - Alam, Moch. Misbahul; Fitriatin, Nur (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
This study aims to analyze student discipline at SMP Buana Waru, focusing on influencing factors and development strategies. The research sample consists of scout members from the elite troop (dewan galang), who are considered to have a strategic role in fostering a culture of discipline among students. A qualitative research approach was employed, utilizing in-depth interviews, participatory observation, and document analysis. The findings reveal that internal factors, such as individual motivation and awareness, and external factors, including support from scoutmasters, peers, and the school environment, significantly contribute to students' discipline levels. Furthermore, the study identifies development strategies that involve a collaborative approach between students, teachers, and parents, as well as reinforcing disciplinary values through extracurricular activities like scouting. The implications of this research provide practical guidance for schools to enhance a culture of discipline through a holistic, character-building-oriented approach.